Iconography beyond the crossroads : image, meaning, and method in Medieval art - Patton, Pamela A., 1964-; Fernandez, Catherine A., 1978- (Signa (Princeton University. Department of Art and Archaeology. Index of Medieval Art), 2022)
This volume assesses how current approaches to iconology and iconography break new ground in understanding the signification and reception of medieval images, both in their own time and in the modern world. Framed by critical essays that apply explicitly historiographical and sociopolitical perspectives to key moments in the evolution of the field, the volume's case studies focus on how iconographic meaning is shaped by factors such as medieval modes of dialectical thought, the problem of representing time, the movement of the viewer in space, the fragmentation and injury of both image and subject, and the complex strategy of comparing distant cultural paradigms. The contributions are linked by a commitment to understanding how medieval images made meaning; to highlighting the heuristic value of new perspectives and methods in exploring the work of the image in both the Middle Ages and our own time; and to recognizing how subtle entanglements between scholarship and society can provoke mutual and unexpected transformations in both. Collectively, the essays demonstrate the expansiveness, flexibility, and dynamism of iconographic studies as a scholarly field that is still heartily engaged in the challenge of its own remaking. Along with the volume editors, the contributors include Madeline H. Caviness, Beatrice Kitzinger, Aden Kumler, Christopher R. Lakey, Glenn Peers, Jennifer Purtle, and Elizabeth Sears.